2017
DOI: 10.15587/1729-4061.2017.112278
|View full text |Cite
|
Sign up to set email alerts
|

Development of an intelligent system for the prognostication of energy produced by photovoltaic cells in smart grid systems

Abstract: watts can operate currently in a common power net. Also, the use of different types of energy sources in one power net can result in power dispersal. This combination of different energy sources makes it possible to instantly respond to load changes at individual sites on the one hand and poses problems in its management on the other hand.The Energorynok State Enterprise is responsible for support of the system ensuring functioning of the wholesale energy market in Ukraine [3,4]. The task of this enterprise is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Paper [8] proposed, in order to improve efficiency of power management, to use forecasts for the generated and consumed electricity. For this purpose, the authors suggested a structure of an expert system based on the use of adaptive neural-fuzzy logic unit for forming a conclusion and controlling information.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Paper [8] proposed, in order to improve efficiency of power management, to use forecasts for the generated and consumed electricity. For this purpose, the authors suggested a structure of an expert system based on the use of adaptive neural-fuzzy logic unit for forming a conclusion and controlling information.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%